2015
DOI: 10.4141/cjps-2014-364
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fungicide and herbicide timing on foliar disease severity, and barley productivity and quality

Abstract: . 2015. The impact of fungicide and herbicide timing on foliar disease severity, and barley productivity and quality. Can. J. Plant Sci. 95: 525Á537. There is interest in mixing herbicides with a half-rate of fungicide at herbicide timings for barley in western Canada. At six sites across the Canadian prairies from 2010 to 2012 combinations of herbicide and the fungicide Tilt † (propiconazole) were applied to barley at the two-to three-leaf stage (herbicide and half-rate fungicide), five-to six-leaf stage (her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Kernel plumpness was not affected by an extra fungicide application in Z32. These results agree with those observed by Turkington et al (2015), whom conducted split applications of fungicide at the time of herbicide application (tillering; earlier than in our study) and at flag leaf emergence and concluded that the split applications did not improve disease management and crop productivity compared with a single full rate fungicide application at the flag leaf stage.…”
Section: Yield Protein and Plumpness Response To Fungicide Application In Z38 (Treatment 4 Vs 3)supporting
confidence: 93%
“…Kernel plumpness was not affected by an extra fungicide application in Z32. These results agree with those observed by Turkington et al (2015), whom conducted split applications of fungicide at the time of herbicide application (tillering; earlier than in our study) and at flag leaf emergence and concluded that the split applications did not improve disease management and crop productivity compared with a single full rate fungicide application at the flag leaf stage.…”
Section: Yield Protein and Plumpness Response To Fungicide Application In Z38 (Treatment 4 Vs 3)supporting
confidence: 93%
“…From a disease management perspective, these results are consistent with Fernandez et al (2014), Turkington et al (2004;, and Poole and Arnaudin (2014), who reported that direct protection of the key upper canopy leaves from cereal leaf disease is critical for maintaining seed yield. Fungicide applications at early crop growth stages, like that used in the current study, will not provide direct protection of upper canopy leaf tissue (Poole and Arnaudin, 2014;Turkington et al, 2004Turkington et al, , 2015. The yield gains could therefore be related to plant responses to prothioconazole that improved plant defense systems against abiotic stress.…”
Section: Treatment Effectsmentioning
confidence: 99%
“…Other studies have suggested that strobilurin fungicides increase water use efficiency of plants under water deficit conditions [19] [21]. Effect of non-disease physiological effects in host plants have been reported to increase soybean yield [22] [23] [24]. Fungicide manufacturers and some researchers have documented crop yield increases following the foliar application of strobilurin fungicide (and some other fungicides) even when there is no disease is visibly present at the time of ap- [24].…”
Section: Introductionmentioning
confidence: 99%